Saint-Saëns and Sophocles. Issue 3 (21st December 2021) - Huebner, Steven
Abstract : Saint-Saëns's incidental music for Sophocles' Antigone (Comédie-Française, 1893, trans. Meurice and Vacquerie) gives witness both to his engagement with culture classique and an experimental orientation in the context of fin-de-siècle music theatre. This essay situates Saint-Saëns's highly idiosyncratic score within the frame of late nineteenth-century research into ancient Greek music by François-Auguste Gevaert and Louis-Albert Bourgault-Ducoudray. It documents how Saint-Saëns aimed to participate in the creation of an authentic experience of ancient Greek theatre, one enhanced by the initiative of the Comédie-Française to stage its production at the open air Théâtre d'Orange in southern France. The article also shows the limitations of authenticity resulting from the nature of the translation as well as from Saint-Saëns's own compositional instincts.